Rainer Werner Fassbinder - Letzte Arbeiten - Gremm, Wolf; Lange, Hartmut (Wolf Gremm - Follow Your Dreams Even If It's Only Just for Fun, 2018)
This short made-for-TV documentary follows Fassbinder at the end of his career, capturing him both as director (at work on his final film, "Querelle") and as actor (in Gremm's "Kamikaze '89", also screening in our retrospective). Gremm's exceedingly rare portrait of his peer and collaborator is an invaluable document of Fassbinder's versatility as a film artist, particularly his ability to simultaneously incarnate the lead role in "Kamikaze '89" and to helm his audacious, career-capping adaptation of Jean Genet. [www.filmlinc.org]